The potential of serum S100 calcium-binding protein B and glial fibrillary acidic protein as biomarkers for traumatic brain injury - Seke Nzau Mafuika; Thajasvarie Naicker; Rohen Harrichandparsad; Lelika Lazarus (Elsevier, 2022)
Background: Traumatic brain injury (TBI) occurs as a result of a severe head injury caused by an external force during a vehicle accident, fall, domestic violence, or explosion. Clinically, TBI is evaluated and classified clinically according to the Glasgow Coma Scale (GCS), associated with Computed Tomography (CT) and Magnetic Resonance Imaging (MRI). However, there are many limitations associated with GCS; therefore, the aim of this review is to perform a systematic meta-synthesis that evaluates the various characteristics of TBI markers. Most especially, S100 calcium-binding protein B (S100B) and Glial Fibrillary Acidic Protein (GFAP). Methods: To achieve this revised review of S100B and GFAP roles in human TBI, an electronic literature search was carried out among articles published in English from previous years up to December 2021. The review included 103 studies and was retrieved from PubMed, Google Scholar, PMC, BMC and Scopus, using the keywords ''traumatic brain injury'' and ''neurobiomarkers''. And ''S100B and GFAP proteins''. Results: & Conclusion: This study demonstrates that S100B and GFAP have a high sensitivity for intracranial injuries and remain unchanged by external factors such as temperature, freeze-thaw cycles, and hemolysis. Moreover, both S100B and GFAP are specific to the brain. Hence a combination of the two proteins could improve the outcome of TBI diagnosis. However, the clinical test value and specific mechanisms of S100B and GFAP to predict TBI requires further investigation.